Magnetic Force Microscopy in Liquids. Issue 36 (6th July 2015) - Ares, Pablo; Jaafar, Miriam; Gil, Adriana; Gómez‐Herrero, Julio; Asenjo, Agustina
<x xml:space="preserve">Abstract</x> In this work, the use of magnetic force microscopy (MFM) to acquire images of magnetic nanostructures in liquid environments is presented. Optimization of the MFM signal acquisition in liquid media is performed and it is applied to characterize the magnetic signal of magnetite nanoparticles. The ability for detecting magnetic nanostructures along with the well‐known capabilities of atomic force microscopy in liquids suggests potential applications in fields such as nanomedicine, nanobiotechnology, or nanocatalysis.